Implementation of Educational Planning: Optimizing the Curriculum to Improve the Efficiency and Quality of Education in the National Education System - Satur, Luzile (Edu Learning, 2025)
Educational planning is the intervention of government institutions, especially in directing and harmonizing national development. This study aims to examine how far education planning, especially in implementing the education curriculum in Indonesia. The method used is a qualitative method with triangulation in obtaining accurate data, in addition to obtaining secondary and primary data to support the accuracy of the researcher’s data. It was found that almost 70% of educational units in Indonesia have implemented the Independent Curriculum. This curriculum gives greater freedom to schools to design learning programs that are in accordance with local needs, focusing on developing students’ creativity and critical thinking skills, However, there are still around 30% of schools that have not implemented it, in its implementation there are challenges in education planning including 1) Low facilities and infrastructure 2) Opportunities for Educational Equity are still low 3) Curriculum changes that are so fast and many more, therefore cooperation between various parties must be optimized to achieve the goals of education planning in Indonesia.